Psychoemotional characteristics in psychosomatic diseases - Karimovna, Narmetova Y.; Khasanboy, Abdusamatov; Iltifotkhon, Abdinazarova; Khabiba, Nurbaeva; Adiba, Mirzayeva (The Scientific Temper, 2023)
It was prepared based on the results of the research conducted at the "Family and Women" Research Institute. This article describes psychoemotional changes in patients with psychosomatic diseases. While the emotions of anger and sadness predominate in patients with cardiological and gastrointestinal diseases, the feeling of fear is more pronounced in patients with endocrinological diseases than other emotional states. In addition, the results of the analysis of the cognitive, emotional, and conative components of the internal appearance of the disease proved that the psychological state of the patient, his attitude to his disease and the treatment process depend on the character of the disease, the possibilities of recovery, the course of the disease and the effectiveness of the treatment.